2006
DOI: 10.1007/s00259-006-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of 11C-choline PET and PET/CT in patients with suspected prostate cancer

Abstract: Based on our findings, differentiation between benign prostatic changes, such as benign prostatic hyperplasia or prostatitis, and prostate cancer is feasible in the majority of cases when image interpretation is primarily based on qualitative characteristics. SUV(max) may serve as guidance. False positive findings may occur due to an overlap of (11)C-choline uptake between benign and malignant processes. By providing functional information regarding both the primary malignancy and its metastases, (11)C-choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 21 publications
3
85
0
6
Order By: Relevance
“…To date, 18 F-FDG PET/CT scans have played only a limited role in the diagnosis or staging of urological malignancies including prostate, bladder, and kidney cancer because of the urinary excretion of 18 F-FDG and variable uptake in some urological cancers (Scher et al, 2007). The specific reasons for its limited use in the diagnosis of prostate cancer are as follows: i) glucose utilization is lower in prostate cancer than in other tumor types; ii) the urinary excretion of 18 F-FDG leads to high bladder activity, which can mask prostate uptake; and iii) the differences between FDG uptake in prostate cancer, benign prostate hyperplasia (BPH), and inflammation are small (Scher et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…To date, 18 F-FDG PET/CT scans have played only a limited role in the diagnosis or staging of urological malignancies including prostate, bladder, and kidney cancer because of the urinary excretion of 18 F-FDG and variable uptake in some urological cancers (Scher et al, 2007). The specific reasons for its limited use in the diagnosis of prostate cancer are as follows: i) glucose utilization is lower in prostate cancer than in other tumor types; ii) the urinary excretion of 18 F-FDG leads to high bladder activity, which can mask prostate uptake; and iii) the differences between FDG uptake in prostate cancer, benign prostate hyperplasia (BPH), and inflammation are small (Scher et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…The specific reasons for its limited use in the diagnosis of prostate cancer are as follows: i) glucose utilization is lower in prostate cancer than in other tumor types; ii) the urinary excretion of 18 F-FDG leads to high bladder activity, which can mask prostate uptake; and iii) the differences between FDG uptake in prostate cancer, benign prostate hyperplasia (BPH), and inflammation are small (Scher et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…12 Mainly 11 C-/ 18 F-choline and 11 C-/ 18 F-acetate seem to be of value for the named indications and superior to FDG-PET, especially in the diagnosis of primary PC. 6,12,[24][25][26][27][28][29][30] However, as in some studies, a differentiation between benign hyperplasia from cancerous lesions of the prostate gland was not possible with for example 18F-fluorocholine PET/CT imaging, all of these tracers still need clinical evaluation with regard to their diagnostic value in PC. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Most reports of 11 C-choline PET imaging involve prostate cancer, although 11 C-choline uptake also is increased in a wide variety of other tumors. 119,120 Given its lack of radiotracer activity in the urine, 11 C-choline is well suited to evaluate pelvic malignancies. 119 In recent studies of patients with prostate cancer, 11 C-choline PET identified recurrent disease in 66% of patients with a mean prostate-specific antigen (PSA) level of 8.3 ng/mL, 28% of patients with a PSA level <1.5 ng/mL, and 21% of patients with a PSA level <0.5 ng/ mL.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%